Hip moment increases while knee and ankle moments remain constant during squats with increasing loads in elite powerlifters - Pürzel, A.; Kaufmann, P.; Koller, W.; Deimel, D.; Baca, A.; Kainz, H. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to investigate compensation strategies among elite powerlifters under high-load conditions. 31 top-ranked powerlifters from the Austrian team executed competition-style squats at 70%, 75%, 80%, 85%, and 90% of their estimated 1-repetition-maximum (Fmax). Employing musculoskeletal modelling, we conducted a biomechanical analysis (i.e. joints moments calculated via inverse dynamics) to understand the alterations in squatting mechanics across various loads. Our findings revealed a consistent relative load shift from the knee to the hip joint with increasing intensity. The knee and ankle joint moments remained constant from 70% to 90% Fmax, underscoring the dominant role of the hip joint in high-load squatting, which indicates that an increasing external load imposes varying relative loads on the hip, knee, and ankle joints during squats.